Systematics and diversity of deep-water Cheilostomata (Bryozoa) from Galicia Bank (NE Atlantic) - Souto, Javier; Berning, Björn; Ostrovsky, Andrew N. (Zootaxa, 2016)
Galicia Bank is a large seamount situated c. 200 km off NW Iberia with a minimum depth of 600 m. It was recently included in Natura 2000, an EU-wide network of nature protection areas. We here present the first taxonomic descriptions of cheilostome bryozoans from this bank. The specimens were collected through the Spanish project INDEMARES (during BANGAL 0811 cruise conducted in 2011) and during two previous campaigns, the French Seamount 1 in 1987 and the German Victor Hensen in 1997). Twenty-five species were found, including 12 that are new to science, while five species remain in open nomenclature. Three new cheilostome genera (Breoganipora, Galiciapora and Placidoporella) are described. A lectotype is designated for Setosella vulnerata (Busk), and Palmicellaria tenuis Calvet is transferred to the genus Porella [as Porella tenuis (Calvet) n. comb.]. Additionally, our study shows that 48–60% of the bryozoan species are endemic to Galicia Bank. The degree of endemism of the Cheilostomata is thus the highest among all orders present on this seamount.